Information, education, and communication services in MCH care provided at an urban health center - Banerjee Bratati (Wolters Kluwer Medknow Publications, 2009)
Background: Regular IEC programs during antenatal and intranatal period, through individual or group approach, brings desirable changes in health practices of people, resulting in a healthy mother and a healthy baby. Materials and Methods: This study was conducted to assess the level of IEC services regarding pregnancy and child care, received by the women at an MCH clinic of an urban health center, where the study subjects comprised 400 antenatal (AN) and postnatal (PN) women and mothers of children under five years. Results: Warning signs of danger was explained to only 10% of the AN and PN women. Advice regarding family planning appeared to be the most frequently covered, though that too was explained to less than half of the subjects. About one third of the women were advised on breast feeding. Only 8% of the mothers had been told about all issues regarding pregnancy and child care. Breast feeding and weaning was properly explained to 85.7 and 81.1% of the total mothers of U5 children. Advice regarding subsequent nutrition was given to 60.9% of mothers. About only a quarter of the total mothers were advised on home management of diarrhea and acute respiratory infections. Very few mothers were counseled about the growth pattern of the children and none were shown the growth chart. Only 12.9% of the mothers were informed about all issues. Conclusion: IEC regarding maternal and child care other than feeding practices is a neglected service in the health facility where the study was conducted.